Analisis Tingkat Daya Saing Cengkeh Indonesia terhadap Negara Pesaing: Tanzania dan Madagaskar - Retnaningsih, Yuli; Indah, Pawana Nur; Laily, Dona Wahyuning (Universitas Galuh, 2024)
Cloves are one of the leading export spice products in Indonesia, however, from 2013 - 2022 they experienced fluctuations. Various problems in the clove trade occur in Indonesia, including clove productivity and the quality produced. This research aims to analyze the level of competitiveness of Indonesian cloves against the countries of Tanzania and Madagascar. This quantitative research uses secondary data as the main data in the form of a time series. The analysis tool used is Revealed Comparative Advantage (RCA). The results of the analysis show that the RCA of Indonesian cloves during 2013 - 2022 shows that it is good with an average value of 18.99 or RCA > 1. The RCA value of Indonesian cloves is still lower than that of Tanzania and Madagascar. However, overall these three countries have comparative advantages.